Hubungan Tingkat Kecerdasan Emosional Dengan Perilaku Caring Perawat Dalam Merawat Pasien Di Rumah Sakit - Ira Ocktavia Siagian; Hudiya; Herwinda Sinaga (Jurnal Keperawatan Muhammadiyah, 2026)
Background: The quality of nursing care is often associated with low caring behavior of nurses, this can be caused by a lack of empathy, low therapeutic communication, and a lack of emotional presence of nurses in providing care. One factor believed to influence caring behavior is emotional intelligence. Emotional intelligence is believed to play an important role in helping nurses understand, respond, and build interpersonal relationships with patients. This study aims to determine the relationship between the level of emotional intelligence and the caring behavior of nurses in caring for patients at Anugerah Bunda Khatulistiwa Hospital, Pontianak. Methods: This study used a quantitative correlational design with a cross-sectional approach. The study population was all 64 inpatient nurses, and the sampling technique used total sampling. The research instruments consisted of the Schutte Self-Report Emotional Intelligence Test (SREIT) to measure emotional intelligence, and the Caring Behaviors Inventory-24 (CBI-24) to measure nurses' caring behavior. Data analysis was performed using the Spearman's Rank correlation test. Results: The results showed that almost half of respondents with high emotional intelligence had good caring behavior (28.1%), and vice versa. Further analysis showed a significant relationship between emotional intelligence and nurses' caring behavior with a p value of 0.003 (<0.05) and a correlation coefficient of r = 0.367. This value indicates a correlation in the low category with a positive direction, which means that the higher the nurses' emotional intelligence, the better the nurses' caring behavior in caring for patients. Conclusion: This finding emphasizes the importance of developing emotional intelligence as an effort to improve the quality of nursing services.